Developing entrustable professional activities for family medicine training in South Africa - Louis S. Jenkins; Robert Mash; Ts'epo Motsohi; Mergan Naidoo; Tasleem Ras; Richard Cooke; Hanneke Brits (South African Family Practice)
Workplace-based assessment (WPBA) is becoming part of high-stake assessments in specialist training. Entrustable professional activities (EPAs) are a recent addition to WPBA. This is the first South African publication on developing EPAs for postgraduate family medicine training. An EPA is a unit of practice, observable in the workplace, constituting several tasks with underlying knowledge, skills and professional behaviours. Entrustable professional activities allow for entrustable decisions regarding competence in a described work context. A national workgroup representing all nine postgraduate training programmes in South Africa has developed 19 EPAs. This new concept needs change management to understand the theory and practice of EPAs. Family medicine departments with large clinical workloads are small, necessitating navigating logistical issues to develop EPAs. It has unmasked existing workplace learning and assessment challenges.